Obesity and long‐term outcomes after incident stroke: a prospective population‐based cohort study. Issue 6 (27th September 2021) - Akyea, Ralph K.; Doehner, Wolfram; Iyen, Barbara; Weng, Stephen F.; Qureshi, Nadeem; Ntaios, George
Abstract: Background: The association between obesity, major adverse cardiovascular events (MACE), and mortality in patients with incident stroke is not well established. We assessed the relationship between body mass index (BMI) and MACE in patients with incident stroke. Methods: The population‐based cohort study identified 30 702 individuals from the Clinical Practice Research Datalink (CPRD GOLD) and Hospital Episode Statistics (HES) databases from the United Kingdom. Individuals were aged ≥18 years with incident stroke between 1‐1‐1998 and 31‐12‐2017, a BMI recorded within 24 months before incident stroke, and no prior history of MACE. BMI was categorized as underweight (<18.5 kg/m 2 ), normal (18.5–24.9 kg/m 2 ), overweight (25.0–29.9 kg/m 2 ), obesity class I (30.0–34.9 kg/m 2 ), class II (35.0–39.9 kg/m 2 ) and class III (≥40 kg/m2). MACE was defined as a composite of incident coronary heart disease, recurrent stroke, peripheral vascular disease (PVD), heart failure, and cardiovascular‐related mortality. Multivariable Cox regression was used to assess differences in MACE risk between BMI categories. Results: At baseline, 1217 (4.0%) were underweight, 10 783 (35.1%) had a normal BMI, 10 979 (35.8%) had overweight, 5206 (17.0%) had obesity Class I, 1749 (5.7%) Class II, and 768 (2.5%) Class III. In multivariable analysis, higher BMI were associated with lower risk of subsequent MACE [overweight: HR 0.96, 95% CI 0.93–0.99)]; PVD [overweight: 0.65 (0.49–0.85); obesity Class III: 0.19 (0.50–0.77)]; cardiovascular‐related death [overweight: 0.80 (0.74–0.86); obesity Class I: 0.79 (0.71–0.88); Class II: 0.80 (0.67–0.96)]; and all‐cause mortality [overweight: 0.75 (0.71–0.79); obesity Class I: 0.75 (0.70–0.81); Class II: 0.77 (0.68–0.86)] when compared to those with normal BMI. The results were similar irrespective of sex, diabetes mellitus, smoking or cancer at time of incident stroke. Conclusions: In patients with incident stroke, overweight or obesity were associated with a more favourable prognosis for subsequent MACE, PVD, and mortality, irrespective of sex, diabetes mellitus, smoking, or cancer at baseline. As with other cohort studies, our study demonstrates an association. Randomized control trials should be considered to robustly evaluate the impact of weight management recommendations on subsequent cardiovascular outcomes in stroke survivors.